Why It Matters What Autocrats Say: Assessing Competing Theories of Propaganda - Constantine Boussalis; Alexander Dukalskis; Johannes Gerschewski (Problems of Post-Communism, 2022)
This article investigates two accounts of political propaganda in autocratic regimes. One argues that propaganda's content does not matter substantively and that propaganda is mostly a signal of the regime's overwhelming power over citizens. A second argues that propaganda is substantively meaningful: autocrats may communicate strategically either by attracting attention through highlighting the regime's strengths or by distracting attention away from the regime's malperformance. Using nearly 135,000 North Korean state-generated news articles between 1997 and 2018 we show that North Korea systematically adjusted its communication strategies following the leadership transfer from Kim Jong Il to Kim Jong Un.
Keywords: 320; Authoritarianism; Autocracy; North Korea; Text-as-data; Propaganda